Alfred Hitchcock's Spellbound - Selznick, David O., 1902-1965; Hitchcock, Alfred, 1899-1980; Bergman, Ingrid, 1915-1982; Peck, Gregory, 1916-2003; Chekhov, Michael, 1891-1955; Carroll, Leo G., 1886-1972; Fleming, Rhonda, 1923-2020; Beeding, Francis (CBS/Fox Video, 1987)
A young man suffering from amnesia and accused of murder is helped by a female psychiatrist who loves him.